2016
DOI: 10.1080/19476337.2015.1136842
|View full text |Cite
|
Sign up to set email alerts
|

Color, phenolic composition and antioxidant activity of blue tortillas from Mexican maize races

Abstract: Cereal products made from pigmented grains are attractive to consumers. We determined the variability in color, phenolic composition and antioxidant activity (AA) of blue tortillas made from 18 landraces belonging to three blue/purple grained Mexican maize races -Chalqueño (Chal), Elotes Cónicos (Ec) and Bolita (Bol). The color of the tortillas produced ranged from yellow-green to bluegreen. Ec tortillas were the only true blue type. Total anthocyanin content (TAC) varied between 3.67 and 1.11 mg equivalents o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
14
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 24 publications
7
14
0
4
Order By: Relevance
“…There are strong differences ( P < 0.05) between the yellow and yellow‐orange varieties. Our results are comparable with the literature, whereas the white and yellow maize varieties show the greatest ( P < 0.05) color vividness in the tortilla (Hernandez‐Martinez et al., ). In our study, they show greater chroma values, indicating that some varieties had less presence of gray and a greater tendency toward color purity ( P < 0.05).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…There are strong differences ( P < 0.05) between the yellow and yellow‐orange varieties. Our results are comparable with the literature, whereas the white and yellow maize varieties show the greatest ( P < 0.05) color vividness in the tortilla (Hernandez‐Martinez et al., ). In our study, they show greater chroma values, indicating that some varieties had less presence of gray and a greater tendency toward color purity ( P < 0.05).…”
Section: Resultssupporting
confidence: 91%
“…Negative a * values indicate a green color in the tortilla. Other authors have also found that blue maize tortilla shows negative a * values (Hernandez‐Martinez et al., ). Of the two varieties producing white flour one (Jellicorse) displayed negative a * values following nixtamalisation.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Se utilizó la herramienta de exploración análisis de componentes principales (ACP) de software STATGRAPHICS Centurión XV para analizar la posible existencia de agrupaciones naturales entre las AT correspondientes a JA S/P y JA P , almacenados a temperaturas de -18, 0, 5 y 10°C y a diferentes tiempos de almacenamiento (17).…”
Section: Análisis De Componentes Principalesunclassified